Determinants of Tax Avoidance in the Infrastructure Sector of State-Owned Enterprises - Vinata, Velia; Dosinta, Nina Febriana; Yantiana, Nella (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The purpose of this study is to determine the influence of capital intensity, return on assets, and firm size on tax avoidance practices. Design/methodology/approach: The data are used from the financial reporting and annual report of the infrastructure sector of state-owned enterprises listed in IDX from 2016-2022. Research Findings: The results of this study indicates that capital intensity has a positive and significant effect on tax avoidance. Meanwhile, return on assets and firm size has no significant effect on tax avoidance. Theoretical Contribution/Originality: The company's capital intensity can reduce tax avoidance efforts in line with fulfilling stakeholder (principal) expectations regarding increasing net income. This research contributes to expanding understanding regarding determinants of tax avoidance and agency theory.